SOSIALISASI TENTANG PERANAN ANALISIS MANAJEMEN RISIKO DALAM PENINGKATAN PRODUKTIVITAS PETUGAS DI UNIT REKAM MEDIS RUMAH SAKIT UMUM ‘AISYIAH PADANG - Dewi Oktavia; Yuli Mardi (LPPM Universitas Bina Bangsa, 2024)
Hospitals as health services institutions have potential dangers and the risk of errors and accidents in serving patients. To ensure the safety of patients and staff in hospitals, as well as prevent unexpected events from occurring, it is necessary to implement a risk management system in all aspects of services provided by hospitals, including in the medical records unit. Implementing a risk management system in the medical records unit will positively impact the work productivity of medical records officers so that it can improve the quality of health services and be profitable for the hospital. The results of previous research at the hospital found that the risk in the filling room was in the moderate risk category at level 3 and high risk at level 4. This of course will affect the productivity of medical records officers. This service aims to provide outreach regarding the role of risk management analysis in increasing the productivity of medical records officers. The expected benefit is to increase the level of knowledge of medical records officers, regarding their role in carrying out risk management analysis in the medical records unit. This service activity is an assisted PKM where the team carries out the first outreach by providing outreach in the form of a lecture, discussing questions and answers, and then continuing with practice in carrying out risk management analysis in the medical records unit at RSU 'Aisyiah Padang. The activity ran smoothly and there was an increase in staff knowledge and understanding regarding risk management in this medical records section. It is recommended that in the future 'Aisyiah Padang RSU be able to implement a risk management system in the medical records unit including the case mix section so that existing risks can be identified, can carry out risk analyzed, and be able to immediately control existing risks to increase the productivity of officer performance